STATE DEBT INSTRUMENTS IN THE FINANCIAL AND CREDIT SYSTEM OF UKRAINE - Levandivskyi, O.T.; Plets, I.I.; Krykhovetska, Z.M. (The actual problems of regional economy development, 2023)
The actuality of the research topic is accompanied by the importance of generalization and scientific substantiation of certain aspects of the functioning of debt financial instruments in Ukraine and in modern global processes in order to learn lessons and outline further tasks of the stock market. The purpose of the study is to determine the essence and features of the development of the state debt securities market, to analyze the trends in its development, the problems of its functioning, and to determine the possible prospects for its development. Government debt securities are the leading instrument used by the state to attract funds for infrastructure development, social programs, and other budget expenditures. In addition, government debt instruments are an important element for the development of the securities market in Ukraine, which contributes to the creation of new opportunities for investors and ensures an increase in the liquidity of the financial market as a whole. The Ukrainian government debt market has undergone six stages of development since independence. The first stage is characterized by the beginning of the birth of the market in 1994-1995, the second stage is characterized by rapid development during 1996-1997. The third stage is associated with the deterioration of the market condition due to the global crisis of 1998. The fourth stage is characterized by the transformation and restructuring processes for 1999-2000. The fifth stage is characterized by the formation of a new model of the government debt market for 2001 - 2007. In the sixth stage, which began in 2008, a significant growth of the market of domestic government loan bonds was observed. The problems arising during the formation, formation and development of the market of public debt obligations in Ukraine are considered. The dynamics of placement of government bonds on the primary market for 2011-2022 were analyzed, in particular the placement of military government bonds in Ukraine. The types of external government loan bonds of Ukraine in circulation were considered. The current practice of issuing government debt securities by the countries of the world, in particular the government of Poland, the USA, Germany, Japan, and the European Commission, is considered. On the basis of the conducted research, directions for improving the functioning of the state debt securities market have been determined. Among them: the introduction of innovative products, the development of international cooperation, public-private partnership tools for financing state projects and programs.